3D Printing Applications in Cardiovascular Medicine - Al'Aref, Subhi J.; Min, James K. (Academic Press, an imprint of Elsevier, 2018)
"3D Printing Applications in Cardiovascular Medicine addresses the rapidly growing field of additive fabrication within the medical field, in particular, focusing on cardiovascular medicine. To date, 3D printing of hearts and vascular systems has been largely reserved to anatomic reconstruction with no additional functionalities. However, 3D printing allows for functional, physiologic and bio-engineering of products to enhance diagnosis and treatment of cardiovascular disease. This book contains the state-of-the-art technologies and studies that demonstrate the utility of 3D printing for these purposes.Addresses the novel technology and cardiac and vascular application of 3D printingFeatures case studies and tips for applying 3D technology into clinical practice Includes an accompanying website that provides 3D examples from cardiovascular clinicians, imagers, computer science and engineering experts"--